Polymorphic markers for identification of parasite population in Plasmodium malariae - Mathema, VB; Nakeesathit, S; Pagornrat, W; Smithuis, F; White, NJ; Dondorp, AM; Imwong, M (BMC, 2020)
Background Molecular genotyping in Plasmodium serves many aims including providing tools for studying parasite population genetics and distinguishing recrudescence from reinfection. Microsatellite typing, insertion-deletion (INDEL) and single nucleotide polymorphisms is used for genotyping, but only limited information is available for Plasmodium malariae, an important human malaria species. This study aimed to provide a set of genetic markers to facilitate the study of P. malariae population genetics.